Genotypic stability and adaptability: analytical methods and implications for cassava breeding for low input agriculture - Dixon, A.; Asiedu, Robert; Hahn, S.K. (1994)
Stable as well as adaptable genotypes of high-yielding cassava cultivars, should be developed and made available to farmers, to ensure increases in cassava production in a target region or country in sub-Saharan Africa. As farmer-to-farmer contact is the primary means of diffusion of new crop varieties, improved cassava cultivars should satisfy farmers' needs for a stable yield from year to year, yet be adaptable to the range of growing conditions that may exist across the targeted area of diffusion. This paper examines the concepts of genotypic stability and adaptability in cassava, using data from several years of cassava multi-locational trials in Nigeria. The cassava breeding scheme at IITA is also described.